2016
DOI: 10.7554/elife.18726
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic neuronal responses to social isolation

Abstract: Many species use social networks to buffer the effects of stress. The mere absence of a social network, however, may also be stressful. We examined neuroendocrine, PVN CRH neurons and report that social isolation alters the intrinsic properties of these cells in sexually dimorphic fashion. Specifically, isolating preadolescent female mice from littermates for <24 hr increased first spike latency (FSL) and decreased excitability of CRH neurons. These changes were not evident in age-matched males. By contrast, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…CRF‐producing neurons are also widely distributed in extrahypothalamic regions, including the bed nucleus of the stria terminalis (BNST), central amygdala (CeA), nucleus accumbens (NAc), and hippocampus, which have, likewise, been implicated in the behavioral and physiological responses to stress. Isolation of preadolescent female (but not male) mice for <24 h decreased the excitability of PVN CRF neurons in a glucocorticoid‐dependent manner . This finding may reflect glucocorticoid feedback–induced suppression of CRF activity.…”
Section: Homeostatic Response To Social Deficit: Promoting Hypervigilmentioning
confidence: 89%
“…CRF‐producing neurons are also widely distributed in extrahypothalamic regions, including the bed nucleus of the stria terminalis (BNST), central amygdala (CeA), nucleus accumbens (NAc), and hippocampus, which have, likewise, been implicated in the behavioral and physiological responses to stress. Isolation of preadolescent female (but not male) mice for <24 h decreased the excitability of PVN CRF neurons in a glucocorticoid‐dependent manner . This finding may reflect glucocorticoid feedback–induced suppression of CRF activity.…”
Section: Homeostatic Response To Social Deficit: Promoting Hypervigilmentioning
confidence: 89%
“…The current study is one of relatively few to use in vitro electrophysiological approaches to directly evaluate function of CRH neurons in PVN (e.g. see Senst et al, 2016; Wamsteeker Cusulin et al, 2013), and the first to do so after chronic salt-loading. It is interesting to note that prior work in rats has indicated that chronic variable stress (CVS) produces an increase in VGluT2 appositions to PVN CRH neurons without altering the number of GABAergic-immunoreactive boutons (Flak et al, 2009), suggesting the possibility that CVS and chronic salt have opposing physiological impact on excitation of CRH neurons.…”
Section: Discussionmentioning
confidence: 99%
“…PVN CRH neurons initiate an endocrine cascade that increases circulating CORT. CORT has been shown to directly (Senst et al 2016) and indirectly (Di et al 2003;Wamsteeker et al 2010) decrease excitability of PVN CRH neurons, but the effects of CORT on GABA transmission are not clear. Reports indicate that CORT either decreases (Verkuyl et al 2004(Verkuyl et al , 2005 or has no effect (Wamsteeker Cusulin et al 2013) on synaptic I Phasic .…”
Section: Introductionmentioning
confidence: 99%